Aryballos and Hanger: an Iconography of a Uniﬁed Entity in Athenian Vase Painting - Young, Yael (Hyperboreus, 2020)
This work examines visual representations of aryballoi and their hangers. Both items are always depicted together, thus creating a uniﬁed entity, that is, separate objects that operate as a unit. Although the aryballos – a small vase primarily employed in a masculine context – is quite conveniently designed for carrying directly in the hand, it is nevertheless always depicted attached to its hanger, and this aﬀects its handling. A comparative case is brought: the alabastron, a vase primarily employed in feminine contexts. Though bearing formal features similar to the aryballos, in visual representations we see the alabastron being handled very diﬀerently, mostly through direct contact and not with a hanger. This leads to the conclusion that vase painters actively gendered vases not only according to type, but even by handling. The combination of aryballos and hanger enables more freedom of movement than the alabastron alone, symbolizing the greater freedom enjoyed by men of the time; while the association of alabastron with women perhaps points to their corresponding lack of freedom. These paintings thus encapsulate and symbolize the diﬀerences between the sexes.